Treatment of the nostrils in patients with cleft lip by a nostril retainer - T. Niimi, N. Natsume, T. Tsukawaki, H. Furukawa, H. Masuda, M. Kobayashi, T. Kawai, (Blackwell Synergy, 2000)
Patients with cleft lip have severe midfacial deformities as a result of the tissue defects of the upper lips and the contraction of scars after the operation, and it is difficult to restore the shape of the nostrils by operation alone.We have therefore used nostril retainers in more than 2000 patients during the period from the first examination to several months after the secondary operation, and observed their condition regularly for several years. We report here our use of nostril retainers.